2017
DOI: 10.1039/c6nr07903b
|View full text |Cite
|
Sign up to set email alerts
|

A 20 nm spin Hall nano-oscillator

Abstract: Spin Hall nano-oscillators (SHNOs) are an emerging class of pure spin current driven microwave signal generators. Through the fabrication of 20 nm nano-constrictions in Pt/NiFe bilayers, we demonstrate that SHNOs can be scaled down to truly nanoscopic dimensions, with the added benefit of ultra-low operating currents and improved power conversion efficiency. The lateral confinement leads to a strong shape anisotropy field as well as an additional demagnetizing field whose reduction with increasing auto-oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
61
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 56 publications
2
61
2
Order By: Relevance
“…Nanoscale, spin current driven [1][2][3], auto-oscillators [4][5][6][7][8][9][10][11] are of great interest both for ultra-wideband microwave signal generation [12,13] and detection [14], and for neuromorphic computing [15][16][17]. A recent subset of these oscillators, so-called spin Hall nano-oscillators (SHNOs) [18][19][20][21][22][23][24][25][26][27][28][29], are driven by pure spin currents injected from an adjacent layer with strong spin-orbit coupling, such as Pt or W, and have demonstrated highly tunable microwave signals at room temperature with frequencies up to 28 GHz [30].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoscale, spin current driven [1][2][3], auto-oscillators [4][5][6][7][8][9][10][11] are of great interest both for ultra-wideband microwave signal generation [12,13] and detection [14], and for neuromorphic computing [15][16][17]. A recent subset of these oscillators, so-called spin Hall nano-oscillators (SHNOs) [18][19][20][21][22][23][24][25][26][27][28][29], are driven by pure spin currents injected from an adjacent layer with strong spin-orbit coupling, such as Pt or W, and have demonstrated highly tunable microwave signals at room temperature with frequencies up to 28 GHz [30].…”
Section: Introductionmentioning
confidence: 99%
“…Spin Hall nano-oscillators [4][5][6][7][8] (SHNOs) rely on SOT to overcome the local spin wave damping and sustain steady-state, current-and field-tunable, precession of the magnetization around an effective magnetic field. SHNOs have been demonstrated using different FM/NM combinations such as NiFe/Pt 5,7,9,10 , NiFe/W 6 , Co 40 Fe 40 B 20 /Pt 11 and YIG/Pt 12 . Finding materials with a high charge-to-spin current conversion, quantified by the spin Hall angle (θ SH = J s /J c ), has been of particular interest, with Pt, Ta 3 , W 6 , AuTa 13 , and CuBi 14 being prominent examples.…”
mentioning
confidence: 99%
“…However, because of the strongly localized injection of spin current in these devices, the solitons were found to be pinned in the active device area, similarly to the conventional NC-STNOs. Another type of SHE nanooscillators that received a significant attention due to their simplicity, geometric flexibility, and efficient operation, are based on a magnetic nanoconstriction [27,[30][31][32]. These devices have been recently utilized to demonstrate 4 SHE-driven magnetization auto-oscillations in magnetic films with PMA [32].…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, a variety of SHE-based STT devices with novel geometries and functionalities have been demonstrated [24]. In particular, it was shown that magnetization dynamics can be excited by SHE [25,26], which led to the development of nanooscillators driven by pure spin currents, which are characterized by moderate heat generation, high oscillation coherence, and efficient tunability of the oscillation frequency [27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%